1987
DOI: 10.1007/bf01611350
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of photopigments in cephalopod retinae

Abstract: The photopigments, rhodopsin and retinochrome, have been localized in cephalopod retinae using light and electron microscopic immunocytochemical methods. Polyclonal antibodies prepared against squid opsin demonstrated the presence of this protein in the photoreceptor rhabdomes, Golgi zone, Golgi-associated vesicles, plasma membrane, large cytoplasmic vesicles, and axonal membranes of octopus retinae. Monoclonal anti-opsin immunostained the rhabdomes and multivesicular bodies in the photoreceptor inner segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
6
18
0
Order By: Relevance
“…10). This distribution was in agreement with the distribution we observed when using electron microscopy (Robles et al, 1987).…”
Section: Opsin Distributionsupporting
confidence: 94%
See 3 more Smart Citations
“…10). This distribution was in agreement with the distribution we observed when using electron microscopy (Robles et al, 1987).…”
Section: Opsin Distributionsupporting
confidence: 94%
“…Immunocytochemical experiments have determined the precise location of opsin and aporetinochrome in cephalopod retinas (Fukushima et al, 1980;Ozaki et al, 1983;Robles et al, 1987). In our electron microscope immunocytochemical studies (Robles et al, 1987), we verified the presence of opsin in the rhabdoms and aporetinochrome in the myeloid bodies.…”
Section: Indexing Terms: Photopigments Rhodopsin Retinochrome Retisupporting
confidence: 69%
See 2 more Smart Citations
“…These structures resemble the lipochondria that are found in the neurons of the abdom inal ganglia of Aplysia californica and that undergo mor phological changes in response to light (Brown et al 1975;Henkhart 1975); these lipochondria are also la belled by antibodies generated against squid opsin (Robles et al 1986). Preliminary studies with this squid opsin antibody have also shown labelling in the B. goul diana eye (Robles et al 1988).…”
Section: Site O F Photon Capturementioning
confidence: 88%